Optimasi Suhu dan Lama Perendaman terhadap Kadar Klorin pada Kertas Rokok Menggunakan Metode Iodometri: Optimization of Temperature and Soaking Time on Chlorine Levels in Cigarette Paper Using the Iodometric Method - Yazid, Edy Agustian; Yaqin, Nur; Zahroh, Roihatul; Salsabila, Dava Isabel (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2025)
Chlorine is a chemical, produced and used throughout the world. Chlorine is usually used as a disinfectant and paper bleach. Cigarette paper is made from materials that are bleached using chlorine. Chlorine is toxic, especially when inhaled, potentially causing eye, skin, respiratory tract irritation and lung damage. The chlorine solubility factor is influenced by temperature and soaking time. This research aims to determine the optimum temperature and soaking time for chlorine levels in filtered cigarette paper (RF) and non-filtered cigarettes (RNF). The research was carried out experimentally with quantitative analysis techniques using the iodometric method. The parameters observed were chlorine levels with temperature variations of 25°C, 50°C, 75°C, 100°C and soaking times of 10 minutes, 15 minutes, 20 minutes, 25 minutes. The research results showed that the highest chlorine levels in RF and RNF paper were 19.26 ppm and 17.88 ppm respectively. The research results concluded that the highest chlorine levels were obtained in RF and RNF paper using the same optimum temperature and soaking time, namely 75°C for 20 minutes. Keywords: chlorine, iodometry, temperature, soaking time, cigarettes Abstrak Klorin merupakan bahan kimia, diproduksi dan digunakan di seluruh dunia. Klorin biasanya digunakan sebagai desinfektan dan pemutih kertas. Kertas rokok dibuat dari bahan yang diputihkan menggunakan klorin. Klorin bersifat toksik terutama bila terhisap, berpotensi menyebabkan iritasi mata, kulit, saluran pernafasan dan kerusakan paru-paru. Faktor kelarutan klorin dipengaruhi oleh suhu dan waktu perendaman. Penelitian ini bertujuan mengetahui suhu dan waktu perendaman optimum terhadap kadar klorin pada kertas rokok filter (RF) dan rokok non filter (RNF). Penelitian dilakukan secara eksperimen dengan teknik analisis secara kuantitatif menggunakan metode iodometri. Parameter yang diamati adalah kadar klorin dengan variasi suhu 25°C, 50°C, 75°C, 100°C dan waktu perendaman 10 menit, 15 menit, 20 menit, 25 menit. Hasil penelitian didapatkan kadar klorin tertinggi pada kertas RF dan RNF berturut-turut 19,26 ppm dan 17,88 ppm. Hasil penelitian disimpulkan kadar klorin tertinggi didapatkan pada kertas RF dan RNF menggunakan suhu dan waktu perendaman optimum yang sama, yaitu suhu 75°C selama 20 menit. Kata Kunci: klorin, iodometri, suhu, waktu perendaman, rokok